2022
DOI: 10.1061/(asce)su.1943-5428.0000399
|View full text |Cite
|
Sign up to set email alerts
|

Houston GNSS Network for Subsidence and Faulting Monitoring: Data Analysis Methods and Products

Abstract: Harris-Galveston Subsidence District (HGSD), in collaboration with several other agencies, has been operating a dense Global Navigation Satellite System (GNSS) network for subsidence and faulting monitoring within the Greater Houston region since the early 1990s. The GNSS network is designated HoustonNet, comprising approximately 250 permanent GNSS stations as of 2021. This paper documents the methods used to produce position time series, transform coordinates from the global to regional reference frames, iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Bertiger et al 47 reported that the GipsyX-PPP daily resolutions achieve approximately 2-3 mm global RMS accuracy in the horizontal direction and 6-7 mm in the vertical direction. According to the previous study in the GOM region, 15,50 the accuracy of the PPP solutions in the GOM coastal region is slightly worse than the global average, mostly because of the humid climates. The RMS accuracy for the daily positions at DEV1 is 4 mm in the NS direction, 3 mm in the EW direction, and 7 mm in the vertical direction (Figure 4).…”
Section: Uncertainty Assessmentsmentioning
confidence: 89%
See 2 more Smart Citations
“…Bertiger et al 47 reported that the GipsyX-PPP daily resolutions achieve approximately 2-3 mm global RMS accuracy in the horizontal direction and 6-7 mm in the vertical direction. According to the previous study in the GOM region, 15,50 the accuracy of the PPP solutions in the GOM coastal region is slightly worse than the global average, mostly because of the humid climates. The RMS accuracy for the daily positions at DEV1 is 4 mm in the NS direction, 3 mm in the EW direction, and 7 mm in the vertical direction (Figure 4).…”
Section: Uncertainty Assessmentsmentioning
confidence: 89%
“…The detailed setup for the PPP processing is the same as the setup for the HoustonNet GNSS data routine processing. 50…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only the datasets from two extensometers (Pasadena, Texas City) among these 13 extensometers show a clear trend of land rebound. There are over one hundred GPS stations in the HGSD Regulatory Areas 1 and 2 (Wang et al 2022); only about a dozen GPS recorded steady land rebound (1 to 2 mm/year), as illustrated in Figure 6. The locations of these GPS stations are marked in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…There is a pair of shallow and deep extensometer boreholes at each of the Clear Lake and Baytown sites. The contour lines indicate the average subsidence rates derived from GPS measurements (2010‐2020) (Wang et al 2022). The dots represent GPS stations that recorded a steady land rebound.…”
Section: Introductionmentioning
confidence: 99%